Occult Carcinoma of the Bronchus - Pearson, F. G. (1966)
The term “occult carcinoma” is applied to those patients with carcinoma of the bronchus at an in situ or early invasive stage who have carcinoma cells in their sputum but have no recognizable evidence of tumour in the chest radiograph. In eight such patients at the Toronto General Hospital, the lesion was localized and treatment instituted. Our experience with these eight patients can be compared with that of 27 patients described in two similar studies. The lesions were commonly symptomatic. Localization, although sometimes difficult, was accomplished using information obtained during bronchoscopy and bronchography. The prognosis following adequate resection appeared excellent. No patient died of carcinoma during the post-treatment follow-up period, which was continued for a minimum of 18 months. Pathological evidence indicates that bronchial carcinoma at this occult stage can be diagnosed cytologically, is rarely multifocal and, as a localized neoplasm, is amenable to curative therapy.